Signal Noise Removal using Concurrent Algorithm - Hammuzamer Irwan , Hamzah (2008)
This research is in the early phase to solve the problem of how to develop a signal noise removal process using concurrent algorithm. The solution of this problem is shown by producing a high level conceptual model to visualize the architecture of this research. The inspiration of human ear by means of the cochlea is adapted for the noise filtering mechanism. Moreover, the brain is utilized as a medium to recognize the filtered signals, make decision, and focus on the desired signal frequency to produce the result. All these processes are concurrently executed to optimize the time and space factors in computing. Therefore, for the moment, a high level conceptual model is introduced to solve this research problem.